EVALUASI STRUKTUR ATAS JEMBATAN GANTUNG PEJALAN KAKI DI DESA AEK LIBUNG, KECAMATAN SAYUR MATINGGI, KABUPATEN TAPANULI SELATAN - Bata Ruddin (Jurnal Teknik Sipil USU, 2017)
ABSTRAK Pedestrian suspension bridge is one type of bridge that only can be crossed bypedestrian and light vehicles such as bicycles, carts, motorcycles and vehicles with amaximum of three-wheel just in case an emergency. The evaluation of pedestriansuspension bridge is based on the reference Enforcement Guidelines for Planning andConstruction Implementation Suspension Bridge Walking For the year 2010 which wasthen aided by SAP 2000. From manual calculations and program will get supportreaction, deflection and ultimate force result of the load acting on bridge. Then there is asuspension bridge Which structural elements are no longer able to withstand the loadthat works and whether deflection occurs is still the limit allowable deflection. Keywords :Suspension bridge, support reaction, deflection, ultimate force.